Investigation of Impact Energy Absorption of AA6061 and Composites: Role of Post-Aging Cooling Methods (Fracture and Structural Integrity, 2023)
Al6061 and its composites are widely employed in applications requiring high strength and impact resistance. Heat treatment, particularly ageing, is a well-established method for enhancing the mechanical properties of these composites. However, the influence of post-ageing cooling methods on the impact energy absorption capacity of Al6061 and its composites remains inadequately understood. This investigation aims to examine the impact energy absorption of Al6061 and its composites after ageing at 460°C for 2 hours, employing different cooling methods, including furnace cooling, air cooling, and water cooling. The composites were produced using the stir casting technique with varying weight fractions of graphite and SiC particles based on Taguchi's design of experiments. Charpy impact tests were conducted using a specialised testing machine. The results reveal that the impact energy absorption capacity of the composites is influenced by the cooling method employed after the ageing treatment. Furnace cooling demonstrated the highest impact energy absorption capacity compared to the other cooling methods, exhibiting a 28% increase compared to the monolithic aluminium alloy. Furthermore, it was observed that the impact energy absorption capacity of the composites did not improve with an increase in the weight fraction of SiC particles, while the addition of graphite negatively impacted the absorption capacity.
Keywords: Al-graphite composite; Metal matrix composite; Impact energy; Al-SiC; Post-ageing cooling